THE MODEL OF VIRTUAL NURSING CARE FOR FUTURISTIC CHALLENGE: A LITERATURE REVIEW - Dwi Yunita Haryanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: To provide an understanding and summarize the challenge regarding the need to be prepared for performing virtual care .Methods: This literature review was conducted through searching 5 databases including ProQuest, Science Direct, PubMed, SAGE, and Google Scholar were searched to identify relevant articles. The strategy used in searching for literature that matches the topic in this literature review uses the PICO framework and then a review was carried out using the PRISMA method to gain insight intothe virtual care nurses.Results: Eight studies met the inclusion out of 45 searchresults. Currently, Virtual nursing care delivery is an innovative strategy to improve patient quality of care. This strategy refers to a variety of healthcare activities delivered remotely using telecommunications and other technologies and this service requires an organized change on nursing management process.Conclusion: Educational preparation includes telenursing as one of the models of nursing care in the nursing education curriculum, developing standards of practice, and certification for Tele nurses to assure patient safety and quality patient outcomes.Â